2019
DOI: 10.1038/s41467-019-11079-y
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite fragmentation induced by massive-like δ–γ transformation in Fe–C alloys

Abstract: Dendrite arm fragmentation is considered in solidification structure tailoring. Time-resolved and in situ imaging using synchrotron radiation X-rays allows the observation of dendrite arm fragmentation in Fe–C alloys. Here we report a dendrite arm fragmentation mechanism. A massive-like transformation from ferrite to austenite rather than the peritectic reaction occurs during or after ferrite solidification. The transformation produces refined austenite grains and ferrite–austenite boundaries in dendrite arms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…In contrast, the observation of dendrite fragmentation via in situ x-ray observation, particularly with the use of synchrotron radiation, has become widespread in recent years. Using automated image processing Liotti et al [28] have demonstrated fragmentation rates in directionally solidified samples which are of the order 10 9 fragmentation events per m 3 per s. Evidence for the detachment and spheriodization of secondary dendrite arms from in situ observation has been provided by a number of authors including Shevechenko et al [29] in a model Ga-In alloy, Zeng et al [30] in SAC Pb-free solder alloys and Yasuda et al [31] in a 0.45 wt.% C steel.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, the observation of dendrite fragmentation via in situ x-ray observation, particularly with the use of synchrotron radiation, has become widespread in recent years. Using automated image processing Liotti et al [28] have demonstrated fragmentation rates in directionally solidified samples which are of the order 10 9 fragmentation events per m 3 per s. Evidence for the detachment and spheriodization of secondary dendrite arms from in situ observation has been provided by a number of authors including Shevechenko et al [29] in a model Ga-In alloy, Zeng et al [30] in SAC Pb-free solder alloys and Yasuda et al [31] in a 0.45 wt.% C steel.…”
Section: Introductionmentioning
confidence: 98%
“…X-ray imaging using synchrotron radiation has allowed observation of the solidification behavior in various metallic alloys such as Sn alloys, [7][8][9][10][11][12][13][14][15][16] Al alloys, 9,10,17,18) cast iron, [19][20][21][22][23] Fe-C steels, 11,[24][25][26][27][28] and stainless steels. 29) Installing a deformation device in the observation apparatus, in-situ observation of semisolid deformation by X-ray transmission imaging (referred to as 2D observation hereinafter) was achieved with a high spatial resolution with respect to grain size.…”
Section: Introductionmentioning
confidence: 99%
“…Premelting may be observed not only at the GBs but also on the surfaces 2,3 and, due to its physically-rich nature and important consequences in wide range of applications, has interested scientists from not only chemistry and physics domains, but also from domains such as earth science 4 , fluid mechanics 5 , and, interestingly, biology 6 . GB premelting has implications in, for example, general metallic systems 1 , steel 7 , and ceramics 8 . It increases GB diffusivity and mobility 9,10 , and can drastically influence the macroscopic properties of a material.…”
mentioning
confidence: 99%